Reporte de un caso de Dirofilaria immitis en un perro. Hallazgo de antígenos y confirmación del parásito a la necropsia (2006)
ABSTRACT: This is a case report of a 3 year old German shepherd native of Medellín city that went to live with his owners to the island of San Andrés at the age of 5 months. The clinical findings were respiratory distress, exercise intolerance, abnormal cardiac sounds and depression. Based on the results of the ancillary tests performed, the patient was diagnosed dirofilariosis and ehrlichiosis. The canine dirofilariosis is a public health concern because human health can be affected, by causing calcified pulmonary nodules. It is necessary to promote the control and prevention of this disease in dogs.